2019
DOI: 10.1088/2399-6528/ab1e82
|View full text |Cite
|
Sign up to set email alerts
|

Ion formation in an argon and argon-oxygen gas mixture of a magnetron sputtering discharge

Abstract: Formation of singly and doubly charged Ar q+ and Ti q+ (q=1,2) and of molecular Ar 2 + , ArTi + , and Ti 2 + ions in a direct current magnetron sputtering discharge with a Ti cathode and argon as working gas was investigated with the help of energy-resolved mass spectrometry. Measured ion energy distributions consist of low-energy and high-energy components resembling different formation processes. Intensities of Ar 2 + and ArTi + dimer ions strongly increase with increasing gas pressure. Addition of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…It can be observed that the thickness of the films for the same sputtering power does not depend strongly on % O2, although a decreasing trend is revealed. Usually, more O2 in the gas mixture might reduce significantly the Rd because of the shielding effect (promoted by the oxidation of the target surface) that decrease the sputtering rate [24]. However, in this study the increase in O2 from 50% to 75% does not seem to significantly affect the thickness of the films.…”
Section: Surface Morphologycontrasting
confidence: 59%
“…It can be observed that the thickness of the films for the same sputtering power does not depend strongly on % O2, although a decreasing trend is revealed. Usually, more O2 in the gas mixture might reduce significantly the Rd because of the shielding effect (promoted by the oxidation of the target surface) that decrease the sputtering rate [24]. However, in this study the increase in O2 from 50% to 75% does not seem to significantly affect the thickness of the films.…”
Section: Surface Morphologycontrasting
confidence: 59%
“…The energy-integrated intensity of Co + is about 40×larger compared to Ar + (figure 7). We want to point out that the measured Ar + ion intensities are rather small in comparison to previous measurements [32,41]. There are at least two reasons, in particular, the smaller ionisation probability of Ar compared to Co due to a larger ionisation energy (15.76 eV compared to 7.88 eV, respectively [42]).…”
Section: Current and Voltage Characteristicsmentioning
confidence: 71%
“…Corresponding numbers for the Ti 2+ /Ti + ratio are 5 × 10 −3 and 3 × 10 −4 for the HC and DCMS discharge, respectively. The numbers are rather common for a standard DCMS discharge [60]. We would like to emphasize that the provided numbers are not corrected for the ion detection efficiency which may depend on the particular ion species and thus have to be taken with some caution.…”
Section: Ion Energy Distributionmentioning
confidence: 99%